Domínguez, Nora. El revés del rostro. Figuras de la exterioridad en la cultura argentina. Rosario: Beatriz Viterbo, 2021 - Rodríguez Pérsico, Adriana; Garramuño, Florencia; Cortés Rocca, Paola; Kratje, Julia; Zangrandi, Marcos; Eltit, Diamela (Badebec, 2022)
n/a